Reduction in Wound Bioburden using a Silver-Loaded Dissolvable Microfilm Construct - Herron, Maggie (2014)
Silver is a widely used antimicrobial agent, yet when impregnated in macroscopic dressings, it stains wounds, can lead to tissue toxicity and can inhibit healing. Recently, we reported that polymeric nanofilms containing silver nanoparticles exhibit antimicrobial activity at loadings and release rates of silver that are 100x lower than conventional dressings. Here we report fabrication of composite microfilm constructs that provide a facile way to transfer the silver-loaded polymeric nanofilms onto wounds in vivo. The construct is fabricated from a silver nanoparticle-loaded polymeric nanofilm that is laminated with a micrometer-thick soluble film of polyvinylalcohol (PVA). When placed on a moist wound, the PVA dissolves, leaving the silver-loaded nanofilm immobilized on the wound-bed. In vitro, the immobilized nanofilms release <1 μg cm(−2)/day of silver over 30 days from skin-dermis and they kill 5 log(10) CFUs of Staphylococcus aureus in 24 h. In mice, wounds inoculated with 10(5) CFU S. aureus presented up to 3 log(10) less bacterial burden when treated with silver/nanofilms for 3 days, as compared to unmodified wounds. In uncontaminated wounds, silver/nanofilms allow normal and complete wound closure by re-epithelialization. We conclude that dissolvable microfilm constructs may overcome key limitations associated with current uses of silver in wound healing.